PERAN ORANG TUA DALAM MENANAMKAN KARAKTER RELIGIUS ANAK DI DESA SUMBER HARAPAN DUSUN SEMBERANG I KECAMATAN SAMBAS KABUPATEN SAMBAS - Patimah Patimah (Tarbiya Islamica, 2016)
The purpose of this was to find out about: 1) The role of parent in instilling religious character in Sumber Harapan village, Dusun Semberang I 2) Knowing the value of religious character instilled by parents in Sumber Harapan Village, Dusun Semberang I. 3) Knowing the role method parent do in instilling religious character in Sumber Harapan village, Dusun Semberang I. This research uses a qualitative approach and this type of research is descriptive. Data collection techniques using interviews, observation and documentation. The technical analysis of the data used is data reduction, data display, verification and drawinf conclusions.